Diabetes Mellitus and Sepsis: A Challenging Association - Trevelin, Silvia C; Carlos, Daniela; Beretta, Matteo; da Silva, João S; Cunha, Fernando Q (Shock (Augusta, Ga.), 2017)
Sepsis is a life-threatening organ dysfunction caused by a deregulated host response to infection. This inappropriate response to micro-organism invasion is characterized by an overwhelmed systemic inflammatory response and cardiovascular collapse that culminate in high mortality and morbidity in critical care units. The occurrence of sepsis in diabetes mellitus (DM) patients has become more frequent, as the prevalence of DM has increased dramatically worldwide. These two important diseases represent a global public health concern and highlight the importance of increasing our knowledge of the key elements of the immune response related to both conditions. In this context, it is well established that the cells taking part in the innate and adaptive immune responses in diabetic patients have compromised function. These altered responses favor micro-organism growth, a process that contributes to sepsis progression. The present review provides an update on the characteristics of the immune system in diabetic and septic subjects. We also explore the beneficial effects of insulin on the immune response in a glycemic control-dependent and independent manner.